Women's Education According To Qasim Amin and Its Implications in The Modern Era: Pendidikan Perempuan Menurut Qasim Amin Serta Implikasinya Di Era Modern - Rafi'na Chalatana (Yayasan Insan Cendekia Nusantara, 2025)
Research Background: This study aims to analyze the concept of women's education proposed by Qasim Amin and its implications in the modern era. Qasim Amin is a reformist thinker from Egypt who is known as a pioneer of the women's emancipation movement in the Islamic world. This research is motivated by the importance of understanding Qasim Amin's thoughts which became one of the milestones in the women's emancipation movement, as well as its relevance in the context of women's education today. This research discusses how the concept and background of women's education thought according to Qasim Amin and how the implications of the concept in the modern era. Methods: The research methodology used is library research with a descriptive-analytical approach, where data is collected through analyzing the texts of Qasim Amin's works as well as related literature and other documents. Key findings: The results showed that Qasim Amin emphasized the importance of education as a means of liberating women from social backwardness and achieving equality for women. Contribution: The implications of the concept of women's education in the modern era can be seen in increasing access to education for women, changing societal attitudes towards the role of women, and gender equality. Conclusion: This conclusion confirms that Qasim Amin's thoughts on women's education have strong relevance in this modern era.